Absence of Association between Methylene Blue Reduced Susceptibility and Polymorphisms in 12 Genes Involved in Antimalarial Drug Resistance in African Plasmodium falciparum - Mathieu Gendrot; Océane Delandre; Marie Gladys Robert; Francis Tsombeng Foguim; Nicolas Benoit; Rémy Amalvict; Isabelle Fonta; Joel Mosnier; Marylin Madamet; Bruno Pradines; on behalf of the French National Reference Centre for Imported Malaria Study Group (MDPI AG, 2021)
Half the human population is exposed to malaria. Plasmodium falciparum antimalarial drug resistance monitoring and development of new drugs are major issues related to the control of malaria. Methylene blue (MB), the oldest synthetic antimalarial, is again a promising drug after the break of its use as an antimalarial drug for more than 80 years and a potential partner for triple combination. Very few data are available on the involvement of polymorphisms on genes known to be associated with standard antimalarial drugs and parasite in vitro susceptibility to MB (cross-resistance). In this context, MB susceptibility was evaluated against 482 isolates of imported malaria from Africa by HRP2-based ELISA chemosusceptibility assay. A total of 12 genes involved in antimalarial drug resistance (Pfcrt, Pfdhfr, Pfmdr1, Pfmdr5, Pfmdr6, PfK13, Pfubq, Pfcarl, Pfugt, Pfact, Pfcoronin, and copy number of Pfpm2) were sequenced by Sanger method and quantitative PCR. On the Pfmdr1 gene, the mutation 86Y combined with 184F led to more susceptible isolates to MB (8.0 nM vs. 11.6 nM, p = 0.03). Concerning Pfmdr6, the isolates bearing 12 Asn repetitions were more susceptible to MB (4.6 nM vs. 11.6 nM, p = 0.005). None of the polymorphisms previously described as involved in antimalarial drug resistance was shown to be associated with reduced susceptibility to MB. Some genes (particularly PfK13, Pfugt, Pfact, Pfpm2) did not present enough genetic variability to draw conclusions about their involvement in reduced susceptibility to MB. None of the polymorphisms analyzed by multiple correspondence analysis (MCA) had an impact on the MB susceptibility of the samples successfully included in the analysis. It seems that there is no in vitro cross-resistance between MB and commonly used antimalarial drugs.